A IMPORTANCE OF MINERAL OILS EXCISE DUTIES FOR CLIMATE POLICY: A COMPARATIVE APPROACH OF THE MACEDONIAN AND EU REGULATION FOR EXCISE DUTIES ON MINERAL OILS - Gjozinska, Biljana; Bulevska Zarik, Adrijana (International Scientific Journal Vision, 2018)
This paper focuses on mineral oils excise duties as an important tool of infl uencing climate policy, and in this context analyze of the Macedonian and EU regulation on mineral oils excise duties. Fossil fuels, which are the base for extraction of mineral oils, comprise over 90% of global energy sources in usage. However, due to their impact on the environment, and with more and more recent studies, on climate change, the regulation of their use, cost and pricing are a signifi cant part of climate policy. The creation of higher excise tax rates on mineral oils implicates a reduced usage of the same in the long run. In Macedonia, as well as in the other countries the most important function of the mineral oils excise duties is regulating the extent of usage of motor oils, in the context of climate policy. However, despite the imposing of excise duties on mineral oils, this tax is still one of the lowest in the region, and far lower than prescribed by EU climate policy.The European Union regulates the usage of all energy sources via the Directive 2003/96, by which the lowest excise duty rates are prescribed for EU member states. The prescribed minimal rates are far above the current excise tax rate on various mineral oils in Macedonia, leading to the conclusion that in the case of EU accession the regulation of excise tax on mineral oils in Macedonia will signifi cantly change.